ANNA SGROSSO through Memory and Future (diségno, 2022)
On April 22nd, 2022, in the magnificent location of palazzo Gravina, the historic headquarters of the University of Naples ‘Federico II’, it was held a memorial day of Anna Sgrosso, a leading figure for the Neapolitan school of Architecture and a national reference point for the scientific-disciplinary sector of Representation of Architecture. [read more]